Information engineering and applications : International Conference on Information Engineering and Applications (IEA 2011) - Ma, Yan; Zhu, Rongbo (Lecture notes in electrical engineering, 2012)
The International Conference on Information Engineering and Applications (IEA) 2011 will be held on October 21-24, 2011, in Chongqing, China. It is organized by Chongqing Normal University, Chongqing University, Shanghai Jiao Tong University, Nanyang Technological University, the University of Michigan, Chongqing University of Arts and Sciences, and sponsored by the National Natural Science Foundation of China. The objective of IEA 2011 is to facilitate an exchange of information on best practices for the latest research advances in the area of information engineering and intelligence applications, which mainly includes computer science and engineering, informatics, communications and control, electrical engineering, information computing, business intelligence and management. IEA 2011 will provide a forum for engineers and scientists in academia, industry, and government to address the most innovative research and development including technical challenges, social and economic issues, and to present and discuss their ideas, results, work in progress and experience in all aspects of advanced information and business intelligence. The conference scope will place emphases on original work on identifying new research and development challenges and developing new techniques and algorithms in information and business intelligence. Original research papers in information and business intelligence on new theories, methods, algorithms, experimental and applied researches are solicited. Authors will be invited to submit complete unpublished papers, which are not under review in any other conference or journal. All tracks are open to both research and industry contributions. The accepted papers will be collected into two volumes of proceedings.